2022
DOI: 10.3390/cells11030564
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes in miR-21 Regulate Right Ventricular Dysfunction in Congenital Heart Disease-Related Pulmonary Arterial Hypertension

Abstract: Right ventricular (RV) failure is a major cause of mortality in pulmonary arterial hypertension (PAH), but its mechanism remains largely unknown. MicroRNA-21 (miR-21) is involved in flow-mediated stress in the vasculature, but its effects on RV remodeling require investigations. Herein, we aim to study the mechanism of miR-21 in the early (compensated) and late (decompensated) phases of PAH-induced RV dysfunction. Using aorto-venous fistula (AVS) surgery, we established a rat model of PAH. To mimic the microen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“… 16 , 28 For example, miR‐21, miR‐130a, and miR‐143/145 are upregulated in the exosomes of patients with PAH and have been shown to promote proliferation, migration, and inflammation in pulmonary artery smooth muscle cells and endothelial cells. 23 , 29 , 30 , 31 We also observed several key miRs with high expression levels in patients with CHD‐related PAH. 30 , 31 Among them, miR‐21 was most significantly activated in HPMECs under flow‐mediated shear stress.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“… 16 , 28 For example, miR‐21, miR‐130a, and miR‐143/145 are upregulated in the exosomes of patients with PAH and have been shown to promote proliferation, migration, and inflammation in pulmonary artery smooth muscle cells and endothelial cells. 23 , 29 , 30 , 31 We also observed several key miRs with high expression levels in patients with CHD‐related PAH. 30 , 31 Among them, miR‐21 was most significantly activated in HPMECs under flow‐mediated shear stress.…”
Section: Discussionmentioning
confidence: 53%
“… 30 , 31 Among them, miR‐21 was most significantly activated in HPMECs under flow‐mediated shear stress. 3 , 23 By suppressing miR‐21 expression levels, shear stress–induced apoptosis was mitigated. 23 Therefore, exosomal miRs could be biomarkers for diagnosis and prognosis of the disease and be used as therapeutic targets for developing new treatments.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a previous article found that the expression of circulating miR-21 of PAH-CHD patients was higher than that of normal controls. However, patients with heart failure had significantly lower expression of circulating miR-21 and left ventricular dysfunction (47). miR-223 is a potential circulating biomarker and small molecule drug for the diagnosis and treatment of PAH.…”
Section: Studies Of Mirna Associated With Pah-chdmentioning
confidence: 99%